Initial Reports of the Deep Sea Drilling Project 1980
DOI: 10.2973/dsdp.proc.54.129.1980
|View full text |Cite
|
Sign up to set email alerts
|

Compositions of Basaltic Glasses from the East Pacific Rise and Siqueiros Fracture Zone, Near 9°N

Abstract: The compositions of 45 natural basalt glasses from nine dredge stations and six Deep Sea Drilling Project Leg 54 sites near 9°N on the East Pacific Rise have been determined by electron microprobe. These comprise 19 distinct chemical groups. Seventeen of these fall in the range of the eastern Pacific tholeiite suite, which is characterized by marked enrichment in FeO*, TiO 2 , K 2 O, and P 2 O 5 as CaO, MgO, and A1 2 O 3 all decrease. Based on trace elements, an estimated 50-75 per cent fractionation of plagio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…For example, in the late 1970s and early 1980s attention focussed on chemical variations as a function of proximity to tectonic offsets along axis such as ridge offsets and propagating rifts [Hekinian and Thompson, 1976;Schilling and Sigurdsson, 1979;Natland and Melson, 1980;Christie and Sinton, 1981;Sinton et al, 1983;Bender et al, 1984;Langmuir and Bender, 1984]. In these and subsequent studies, evidence was found for local variations in the extent of melting and degree of fractionation.…”
Section: Local Variability and Ridge Segmentationmentioning
confidence: 98%
“…For example, in the late 1970s and early 1980s attention focussed on chemical variations as a function of proximity to tectonic offsets along axis such as ridge offsets and propagating rifts [Hekinian and Thompson, 1976;Schilling and Sigurdsson, 1979;Natland and Melson, 1980;Christie and Sinton, 1981;Sinton et al, 1983;Bender et al, 1984;Langmuir and Bender, 1984]. In these and subsequent studies, evidence was found for local variations in the extent of melting and degree of fractionation.…”
Section: Local Variability and Ridge Segmentationmentioning
confidence: 98%
“…The transform edge effect has become part of the litany of possible effects which are commonly cited to account for variations in crustal thickness (Fox, et al, 1980) and in basalt composition seen near to fracture zones (Natland and Melson, 1980;Perfit, et al, 1983;Bender, et al, 1983;Langmuir and Bender, 1984). A case can be made that there has not yet been a definitive demonstration of a transform edge effect.…”
Section: Fractionation Historymentioning
confidence: 97%
“…It has long been postulated that transform faults have an effect on the composition and structure of the nearby oceanic crust (Fox, et al, 1980;Natland and Melson, 1980;Stroup and Fox, 1981;Langmuir and Bender, 1.984). This effect is thought to be due to the conduction of heat across the transform away from the active ridge segment.…”
Section: Dedicated To Laetitia Mary Harrermentioning
confidence: 99%
See 2 more Smart Citations